Intrarenal infusion of gallopamil in acute renal failure. A preliminary report - Lumlertgul D. (2014)
In order to ascertain the protective role of a potent calcium entry blocking agent in human acute renal failure, 10 patients were randomised to treatment with either intrarenal gallopamil plus intravenous furosemide (frusemide) 0.5 mg/kg/h for 24 hours, or furosemide alone. Gallopamil was infused into each kidney at the rate of 40 to 80 micrograms/min for 4 hours. During 7 days of post-treatment follow-up, the gallopamil treatment group exhibited a significantly higher urine output [257 ml/h vs 81 ml/h (p less than 0.001) after 2 days, and 199 ml/h vs 120 ml/h (p less than 0.005) after 7 days] and creatinine clearance [20 vs 4 ml/min (p less than 0.005) after 2 days, and 38 vs 14 ml/min (p less than 0.001) after 7 days] than the furosemide-only control group. Furthermore, gallopamil treatment accelerated the decline of serum creatinine after renal failure and reduced the requirement for dialysis. Although patient numbers were small, these results indicate that the addition of intrarenal gallopamil to intravenous furosemide treatment enhances the recovery of renal function after acute renal failure.